The illusion of abundant communications and the ghost of Red Lion - Burstein, Michael J. (Frontiers in Research Metrics and Analytics, 2022)
Twentieth-century communications law was built on the assumption of scarcity—radio spectrum as a scarce natural resource and telephone networks as a natural monopoly. Scarcity justified both rate regulation and content regulation of the services offered over these communications resources. Telephone networks were subject to the nondiscrimination rules of common carriage, and the Supreme Court in Red Lion Broadcasting v. FCC famously upheld the “fairness doctrine,” which required that both sides of public issues be discussed fairly over broadcast media, expressly on the rationale that the scarcity of the airwaves justified content-based regulation under the First Amendment. As the century drew to a close, however, technological developments cast doubt on the assumption of scarcity and, therefore, much of the legal framework of communications law. In this chapter, I explain how both incumbent and startup providers reacted to this seeming technological abundance with acts aimed at recreating scarcity—strongly resisting encroachments on exclusive franchises or collusively slowing or halting the rollout of alternative networks—and how communications law has failed to keep up. It’s widely acknowledged that our current statutory law is maladapted to modern technology, but in this work I recast the ongoing fights over net neutrality, affordable broadband, and platform speech regulation in terms of scarcity and abundance and argue that Red Lion is still with us in spirit—communications law should address the sources and effects of new scarcity. I sketch out what such regulation might start to look like and conclude with some thoughts about what this story means for the central thesis of this volume.